On the Existence of Chaos for the Fourth-Order Moore–Gibson–Thompson Equation - Lizama-Yanez, C (Elsevier Ltd, 2023)
We analyze the existence of chaos for the fourth-order Moore–Gibson–Thompson equation. We obtain sufficient conditions on the parameters of the equation so that it exhibits a chaotic behavior in the Devaney sense. Such dynamic behavior is achieved in Herzog-like spaces revealing the structure of critical parameters. © 2023 Elsevier Ltd